THE ROLE OF MEMORY PROCESSES IN INCREASING EDUCATIONAL EFFICIENCY (Universal International Scientific Journal, 2026)
This article analyzes the issues of improving teaching methods in the modern educational process, taking into account the characteristics of students' memory. It covers the types of memory, the stages of encoding and restoring information based on the theories of world psychologists. It is explained that in order to increase the effectiveness of education, a teacher must not only know his subject, but also have a deep understanding of student psychology and memory mechanisms.
Keywords: memory, educational effectiveness, recall, retrieval, attention, primary education, pedagogical technology.